2021
DOI: 10.4236/ojn.2021.1110068
|View full text |Cite
|
Sign up to set email alerts
|

How Do Patients Prefer to Receive Patient Education Material about Treatment, Diagnosis and Procedures? <br/>—A Survey Study of Patients Preferences Regarding Forms of Patient Education Materials; Leaflets, Podcasts, and Video

Abstract: Aim: The aim of this study was to explore patients' preferences for forms of patient education material, including leaflets, podcasts, and videos; that is, to determine what forms of information, besides that provided verbally by healthcare personnel, do patients prefer following visits to hospital? Methods: The study was a mixed-methods study, using a survey design with primarily quantitative items but with a qualitative component. A survey was distributed to patients over 18 years between May and July 2020 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
3
0
3
Order By: Relevance
“…Educational programs are a key component of disease management for a variety of medical conditions and may improve clinical outcomes and self-efficacy; however, outcomes vary considerably between different programs, and the key factors that improve success are unclear [ 39 ]. Patient preferences for education may affect these differing outcomes [ 39 , 40 ]. Clinicians should therefore explore information needs with their patients, and offer tailored information, such as written pamphlets and websites (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Educational programs are a key component of disease management for a variety of medical conditions and may improve clinical outcomes and self-efficacy; however, outcomes vary considerably between different programs, and the key factors that improve success are unclear [ 39 ]. Patient preferences for education may affect these differing outcomes [ 39 , 40 ]. Clinicians should therefore explore information needs with their patients, and offer tailored information, such as written pamphlets and websites (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Et dansk studie viser desuden, at en kombination af skriftlig og visuel information hjaelper på forståelsen (11). Film er en informationsform, som børn og unge kender rigtigt godt, og dermed vil en informationsfilm som supplement til vanlig skriftlig og mundtlig information formentlig gøre, at børn og unge oplever at vaere endnu bedre forberedt, hvilket vil give dem den bedste forudsaetning for at gennemføre FP og få afklaret deres allergi.…”
Section: Litteraturenunclassified
“…Resultaterne haenger dog godt sammen med et dansk studie, der viser, at mange patienter ønsker adgang til både skriftlig, visuel og auditiv information (11). Studiet inkluderer dog kun voksne, men da børn og unge er endnu mere vant til visuel og digital information og kommunikation end mange voksne er, må man formode, at det samme gør sig gaeldende for dem.…”
Section: Analysemetoderunclassified
See 1 more Smart Citation
“…Additionally, for people with ADHD comprehension of written information is worse when the information is delivered digitally rather than in print (36). Another study of how people prefer to receive healthcare information found that participants value a combination of written, audio and video materials, suggesting that the most useful source of information would utilise multimodal communication methods (37). It is important to consider some limitations of these studies -the samples were generally small, and from limited populations, such as a single clinic, university, or level of education, which limits the generalisability of the results.…”
Section: Enhance Digital Delivery Using Social Supportmentioning
confidence: 99%